1999
DOI: 10.1038/sj.onc.1203048
|View full text |Cite
|
Sign up to set email alerts
|

Human POMp75 is identified as the pro-oncoprotein TLS/FUS: both POMp75 and POMp100 DNA homologous pairing activities are associated to cell proliferation

Abstract: We have previously developed an assay to measure DNA homologous pairing activities in crude extracts: The POM blot. In mammalian nuclear extracts, we detected two major DNA homologous pairing activities: POMp100 and POMp75. Here, we present the puri®ca-tion and identi®cation of POMp75 as the pro-oncoprotein TLS/FUS. Because of the pro-oncogene status of TLS/FUS, we studied in addition, the relationships between cell proliferation and POM activities. We show that transformation of human ®broblasts by SV40 large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 64 publications
(59 reference statements)
2
69
0
Order By: Relevance
“…These data agree with a role of TLS in transcriptional regulation. TLS has been biochemically characterized as hPOMp75, a protein involved in homologous DNA pairing and recombination (Baechtold et al, 1999;Bertrand et al, 1999). This activity fits with the increased sensitivity to ionizing radiation due to chromosome pairing defects during meiosis in the TLS-deficient mice suggesting that TLS could participate to the maintenance of genomic integrity (Kuroda et al, 2000).…”
Section: Introductionmentioning
confidence: 85%
“…These data agree with a role of TLS in transcriptional regulation. TLS has been biochemically characterized as hPOMp75, a protein involved in homologous DNA pairing and recombination (Baechtold et al, 1999;Bertrand et al, 1999). This activity fits with the increased sensitivity to ionizing radiation due to chromosome pairing defects during meiosis in the TLS-deficient mice suggesting that TLS could participate to the maintenance of genomic integrity (Kuroda et al, 2000).…”
Section: Introductionmentioning
confidence: 85%
“…Indeed, analysis of TLS-deficient mice suggests a possible role of TLS in both repairing DNA damage (12) and maintaining genomic integrity (13). According to these biological data, various biochemical studies identified TLS as a protein involved in pairing DNA sequences during homologous recombination (14,15).…”
Section: Tls (Translocated In Liposarcoma)mentioning
confidence: 99%
“…Indeed, analysis of TLS-deficient mice suggests a possible role of TLS in both repairing DNA damage (12) and maintaining genomic integrity (13). According to these biological data, various biochemical studies identified TLS as a protein involved in pairing DNA sequences during homologous recombination (14,15).Other data argue for a role of TLS in regulation of gene transcription. TLS as EWS and the highly similar factor hTAFII 68 have been purified in distinct TFIID complexes associated with the RNA polymerase II (16,17).…”
mentioning
confidence: 99%
“…For example, a recent study has shown the involvement of hnRNPA1 in Okazaki fragment maturation during DNA replication as a stimulator of the FEN-1 nuclease (33). A novel role of another ribonucleoprotein, this time in genome maintenance, has also been demonstrated; the TLS/FUS protein has been shown to mediate homologous pairing and to be involved in the DNA damage response (34). The TASR (TLS-associated SR) proteins, identified as being involved in DPCs in our study, may also be involved in these processes because of their association with TLS.…”
Section: Discussionmentioning
confidence: 99%